A Model for Mobile Payment in Ubiquitous Commerce - Roehrs, Alex; Costa, Cristiano André da; Barbosa, Jorge Luis Victória (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2011: Anais do XII Simpósio em Sistemas Computacionais de Alto Desempenho, 2011)
This paper aims at presenting an architectural model proposal for a novel Mobile Payment System, called 4iPay. This work considers the following premises: independence of device, location, carrier and cardholder to meet the needs of executing payment transactions in ubiquitous commerce. Our proposal considers the convergence of concepts of ubiquity, unity, universality and unison to form the proposed model. This article describes the model, implementation, preliminary assessments and requirements for mobile payment in ubiquitous environments. We developed a prototype of 4iPay using Android smartphones. Our protoype was evaluated in three diferente scenarious.